Rotal Anthology. An Annotated Index of Rotal Decision from 1971 to 1988, Compiled by Augustine Mendoça. Washington D. C. ohne Angabe [Rezension] - Fedele, Pio (1993)
Sammlung von Urteilen der Rota Romana (1971-1988)
Keywords: Katholische Kirche -- Rota Romana; Rechtsprechung; Rezension